[Letters to Congress members from Lorillard] (Tufts Archival Research Center, 2007)
Lorillard letters to Congress members. Thanks them for taking the time to meet with Lorillard representatives. Offers "reasonable assistance" to aid Congress members. Indicates that Lorillard will keep in touch.